Coal and coalbed gas : fueling the future - Flores, Romeo M. (Elsevier, 2014)
This book discusses the processes of coalification, gasification, and storage and reservoir characterization and evaluation, as well as environmental issues encountered in the development of coalbed gas. Case studies, field guides and data, examples, and analytical procedures from previous studies and investigations are also included.